Analisis rasio yang mempengaruhi stock return pada perusahaan sektor perbankan syariah - Elza Farenza Rahmawan; Rofiuddin, Mohammad (Journal of Economics Research and Policy Studies, 2023)
This study aims to determine the effect of earnings per share, debt-to-equity ratio, and changes in net profit on stock return with price-to-book value as a mediator. This research is quantitative, with analytical tools in the form of path analysis and mediation testing using the Aroian test. The population used is the financial sector companies listed on the Indonesia stock exchange. The sampling technique is purposive sampling. With the provisions of the listed Sharia banking sector companies, having verified financial statements and actively transacting shares on the IDX from q2 2018 to q1 2021. Based on the t-test results, the earning per share variable hurts stock returns, but the debt-to-equity ratio and changes in profit do not affect stock returns. In contrast, price-to-book value positively affects stock returns. Earnings per share positively affect the price-to-book value, while the debt-to-equity ratio and net profit do not affect the price-to-book value. The results of the Aroian test found that only earnings per share on stock returns could be mediated by price to book value. Meanwhile, price-to-book value cannot mediate the debt-to-equity ratio and net profit.